2011
DOI: 10.1021/cn200018v
|View full text |Cite
|
Sign up to set email alerts
|

ANCA: A Family of Fluorescent Probes that Bind and Stain Amyloid Plaques in Human Tissue

Abstract: A new family of fluorescent markers containing an Amino Naphthalenyl-2-Cyano-Acrylate (ANCA) motif has been synthesized and evaluated for its capability to associate with aggregated β-amyloid (Aβ) peptides. These fluorescent probes contain a nitrogen donor group that is connected via a naphthalene unit to an electron acceptor motif containing Water Solubilizing Groups (WSG). Chemical modifications were introduced to explore their effect on the capability of the ANCA-based probes to fluorescently label aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 38 publications
4
85
0
Order By: Relevance
“…Fluorescence molecular imaging is appealing for small animal studies because of its low cost, easy operation, and stable imaging probes. In the past decade, the development of fluorescent imaging probes for AD has been actively pursued, and several probes showed capacity for imaging Aβs (37)(38)(39)(40)(41)(42)(43)(44)(45) and Tau tangles (64) in mice. Nonetheless, none has been used to monitor the effectiveness of drug therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence molecular imaging is appealing for small animal studies because of its low cost, easy operation, and stable imaging probes. In the past decade, the development of fluorescent imaging probes for AD has been actively pursued, and several probes showed capacity for imaging Aβs (37)(38)(39)(40)(41)(42)(43)(44)(45) and Tau tangles (64) in mice. Nonetheless, none has been used to monitor the effectiveness of drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several NIRF probes for insoluble Aβs have been reported (37)(38)(39)(40)(41)(42)(43)(44)(45). It has been almost 10 y since the first report of NIRF imaging of Aβs by Hintersteiner et al in 2005 (41).…”
mentioning
confidence: 99%
“…However, there have been fewer reports regarding the development of fluorescent probes than PET probes despite their significance, although AOI-987, 29 NIAD-4, 30 CRANAD-2, 32 ANCA-11, 35 and BMAOI 36 have been reported for the imaging of Aβ plaques.…”
mentioning
confidence: 99%
“…In principle, an ideal fluorescent probe for Aβ should have the following properties [35][36][37][38] : (1) a high selectivity and a binding affinity for Aβ; (2) a high quantum yield and a significant change in fluorescence upon binding to Aβ; (3) a suitable emission wavelength greater than 450 nm to minimize background fluorescence from brain tissue, ideally between 650 nm and 900 nm for in vivo detection; (4) the ability to rapidly cross the blood-brain barrier (BBB); (5) a high metabolic stability; (6) fast washout kinetics from normal brain regions; (7) low toxicity; and (8) straightforward synthesis.…”
Section: What Makes An Ideal Aβ Fluorescent Probe?mentioning
confidence: 99%
“…One of these compounds, ANCA-11 (37), showed increased fluorescence upon binding to Aβ aggregates (7.7-fold) and the highest binding affinity (K d =1.4 μmol/L) among all compounds. In vitro tests indicated that all of the compounds could fluorescently stain amyloid deposits in human brain tissue from AD patients [35] . However, further improvement of the binding affinity and maximal emission wavelengths of these probes is needed.…”
Section: Other Probesmentioning
confidence: 99%